Esophageal Lichen Planus as a Cause of Dysphagia: Literature Review and Clinical Observation - A. I. Dolgushina; E. R. Olevskaya; A. O. Khikhlova; A. A. Saenko; S. U. Belousov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to analyze the literature data, and to raise awareness of doctors of various specialties about the methods of diagnosis and treatment of esophageal lichen planus (ELP).Key points. In a 67-year-old female patient with complaints of difficulty swallowing solid food and weight loss, esophagogastroduodenoscopy revealed subcompensated stenosis of the middle third of the esophagus and signs of fibrinous esophagitis. Based on the characteristics of the endoscopic picture and the detection of apoptotic Ciwatt bodies in esophageal biopsies, a diagnosis of ELP was established. Treatment with glucocorticosteroids led to relief of symptoms and positive endoscopic dynamics. ELP is rare and the least studied, data on this disease in the literature are presented mainly in the form of clinical observations and analysis of series of cases. Typical clinical manifestations include dysphagia and odynophagia. Despite the low prevalence, ELP can be associated with serious complications: stenosis and esophageal squamous cell carcinoma. Endoscopic examination reveals characteristic signs in the esophagus: swelling, thickening and increased vulnerability of the mucosa, often with fibrin, formation of membranes and strictures. The histological picture is represented by epithelial dyskeratosis with exfoliation, lichenoid lymphocytic infiltration. The most specific histological sign is the presence of apoptotic Civatte bodies. Recommendations for the treatment of ELP are limited to the results of a series of clinical observations and include the prescription of systemic corticosteroids. The issue of supportive therapy is the least studied.Conclusion. Analysis of the literature data and the clinical case demonstrate that lichen planus of the esophagus is one of the rare causes of dysphagia. Characteristic endoscopic and histological signs are key for the diagnosis. The management of patients with esophageal lichen planus is insufficiently defined and today includes taking of glucocorticosteroids, endoscopic dilation of stricture and dynamic endoscopic observation, given the high risk of squamous cell carcinoma in this category of patients.